A Conceptual Model to Achieve Health Equity in APOL-1 Clinical Studies - Raven A. Hardy Richard; Rebecca Hayes; Robert Flemming; Cesia Portillo; Richardae Araojo; Christine Lee (Health Equity)
The socioecological model (SEM) conceptualizes health broadly and focuses on multiple factors that might affect health. This article takes a novel approach to leverage an SEM framework to identify challenges and sustainable opportunities to advance diversity for clinical study participation in apolipoprotein L1 (APOL-1)-mediated kidney disease. We describe four levels of an APOL-1 SEM—intrapersonal, interpersonal, community, and structures/systems—for improved diverse APOL-1 clinical study enrollment and engagement. This SEM can serve as a model for improving clinical study diversity and equity to help improve the generalizability of clinical study results in other disease conditions that disproportionally impact racial and ethnic minority populations.